THE DEVELOPMENT OF LEADERSHIP MODEL FOR THE ENHANCEMENT OF PASTORAL CARE SKILLS FOR SEMINARIANS IN VIETNAM - NGUYEN, HA; ASAVISANU, POONPILAS (Scholar: Human Sciences, 2022)
The purpose of this study was to develop a leadership model for the enhancement of pastoral care skills of seminarians in Vietnam. Both qualitative and quantitative methods were applied during the study, which included document study and content analysis, interviews, and questionnaires to find the desirable pastoral and leadership characteristics and to determine the gap between the current and desired characteristics of the parish priests. The participants of the study included 2,308 seminarians and parishioners from six seminaries in Vietnam. Data analysis was conducted using descriptive statistics and inferential statistics. A paired-samples t-test and Pearson correlation were conducted. The findings from the study revealed the following eight characteristics relevant to pastoral care: Protection, Wisdom, Sanctity, Humility, Creativity, Courage, Confidence, and Care. A paired-samples t-test was conducted on pastoral characteristics for both the current and expected states. There was a significant difference in the scores for CPC (M = 3.62, SD = 0.51) and EPC (M = 4.07, SD = 0.39); t (2,308) = 40.263, p = .000. A paired samples t-test was also conducted on leadership characteristics for both the current and expected states. A significant difference was also found for the CLC (M = 3.56, SD = 0.55) and ELC (M = 4.07, SD = 0.46); t (2,308) = 40.497, p = .000. The statistical findings indicated that there was a difference in the expectations of parishioners and seminarians in the pastoral care they were receiving and the expected and current leadership characteristics of their parish priests. This supports the need for a model to be implemented during seminarians’ training to carry out their future responsibilities as parish priests more effectively. A subsequent model was developed incorporating the eight characteristics of pastoral care and leadership and sent to religious experts for approval and validation.